FINDING SHORTEST PATH BASING ON DIJKSTRA'S ALGORITHM FOR BAGHDAD UNIVERSITIES BY USING GEOGRAPHIC INFORMATION SYSTEM APPLICATIONS - Roaa Ebada Saeed,; Amer Saleem Elameer,; Rafah Shahab Alhamdani, (QALAAI ZANIST JOURNAL, 2021)
As the population increases, the transport network becomes difficult and enormous. Finding demanded location is becomes a troublesome task. After finding, a location individual gets confused to access that location because of the routes contains several modes. This drawback is even more substantial for those who may have to go to strange parts of the city. Just in case of the universities, it is troublesome to find the specified university and it's the shortest path to access therefore takes longer to access it. In this paper solved this problem by find the shortest path from the user location to the university or between two universities. The area for study is Baghdad city and the coordinate for universities is obtained from Google earth program. The ArcGIS software system used and also the Dijkstra’s algorithm to produce the shortest path from one location to a different and ArcGIS cloud publisher for publish map from ArcMp to ArcGIS cloud and then can be edited and updated